Europe's Growth Emergency - Zsolt Darvas; Jean Pisani-Ferry (Hungarian Academy of Sciences, Institute of Economics, 2011)
Highlights: - The European Union growth agenda has become even more pressing because growth is needed to support public and private sector deleveraging, reduce the fragility of the banking sector, counter the falling behind of southern European countries and prove that Europe is still a worthwhile place to invest. - The crisis has had a similar impact on most European countries and the US: a persistent drop in output level and a growth slowdown. This contrasts sharply with the experience of the emerging countries of Asia and Latin America. - Productivity improvement was immediate in the US, but Europe hoarded labour and productivity improvements were in general delayed. Southern European countries have hardly adjusted so far - There is a negative feedback loop between the crisis and growth, and without effective solutions to deal with the crisis, growth is unlikely to resume. National and EU-level policies should aim to foster reforms and adjustment and should not risk medium-term objectives under the pressure of events. A more hands-on approach, including industrial policies, should be considered.
Keywords: E60; F43; O40; 330; economic growth; deleveraging; productivity; convergence; economic adjustment; structural reform scoreboard; composition of fiscal adjustments; growth policy under constraints; Wirtschaftskrise; Wirtschaftswachstum; Wachstumspolitik; Investitionspolitik; Wirtschaftsreform; EU-Staaten